Endogenous Enforcement and Effectiveness of China's Pollution Levy System - Wang, Hua (World Bank, Washington, DC, 2015)
The authors investigate two aspects of China's pollution levy system, which was first implemented about 20 years ago. First, they analyze what determines differences in enforcement of the pollution levy in various urban areas. They find that collection of the otherwise uniform pollution levy is sensitive to differences in economic development and environmental quality. Air and water pollution levies are higher in areas that are heavily polluted. Second, they analyze the impact of pollution charges on industry's environmental performance, in terms of the pollution intensity of process production and the degree of end-of-pipe abatement for both water pollution and air pollution. Econometric analysis shows that plants respond strongly to the levy by either abating air pollution in the production process or providing end-of-pipe treatment for water pollution.